(untitled) (Global Journal of Medical Research, 2014)
Since the beginning of human history, mankind has been asking a very simple question, "what is mind?. As humans developed in the path of science and philosophy, this question became more and more complex with thousands of other doubts and confusions emerging from it. Back in the days, when humanity had just discovered fire, if somebody behaved unnaturally or crazy, collective ignorance defined it as some supernatural possession. Even today, to our disgrace, this ignorance runs through the profound and remote veins of many civilizations. But, thinkers throughout history dared to ask questions to unfold these mysteries of human behavior. Freud and Breuer took a step further in the clandestine arena of human mind, by finding out jewels of facts behind Hysteria. Following the footsteps of Freud, another man named C.G. Jung, made us more aware about the truth behind the most subtle acts of human psychology. On the pillars of all these rising knowledge, modern neurology became far more delicate and sophisticated, shedding light over different dark regions of the brain.